Impact of Hashimoto's thyroiditis, TSH levels, and anti-thyroid antibody positivity on differentiated thyroid carcinoma incidence - Gabalec, Filip; Srbova, Libuse; Nova, Marketa; Hovorkova, Eva; Hornychova, Helena; Jakubikova, Iva; Ryska, Ales; Cap, Jan (Endokrynologia Polska, 2016)
INTRODUCTION: The relationship between Hashimoto's thyroiditis (HT) and thyroid cancer (TC) is controversial. While most surgical studies report a high incidence of malignancy among patients with HT, cytological studies do not. The role of autoantibodies in the incidence of malignancy is unclear. MATERIAL AND METHODS: A single-centre retrospective observational study was conducted in patients evaluated for thyroid nodules by US-guided fine-needle aspiration cytology (FNAC) and, if indicated, by surgery. The levels of thyroid-stimulating hormone (TSH) and anti-thyroid antibodies were measured at the time of FNAC. RESULTS: Of 4947 patients, 599 (12.1%) were diagnosed with HT. A malignant/suspicious cytological result was found in 14.2% of the patients with HT and in 15.2% of the others. The odds ratio (OR) for malignancy in HT was 0.921 (0.716-1.183, p = 0.51). Of 1603 patients who underwent surgery, differentiated thyroid carcinoma was found in 29.5% of the HT patients and in 15.2% of the others (OR 2.33, 95% confidence interval CI, 1.403-3.854, p < 0,001). Low TSH (< 0.4 mIU/L) decreased the malignancy rate in the entire patient population, both when considering the cytological results and the surgical results. This was not confirmed in the subgroup diagnosed with HT. No relationship was observed between autoantibodies against thyroid peroxidase (ATP) or thyroglobulin (ATG) and malignancy rate. CONCLUSIONS: No association between HT and thyroid cancer was observed cytologically; a positive relationship in histological series was caused by selection bias. Low TSH levels decreased the risk of TC in patients with nodular goitre, but this has not been proven in patients with HT.
Keywords: štítná žláza; nádory štítné žlázy; retrospektivní studie; Humans; Hashimoto Disease; Autoantigens; biopsy; fine-needle biopsy; Iodide Peroxidase; incidence; mužské pohlaví; proteiny vázající železo; thyreoglobulin; Thyroid Neoplasms; autoantigeny; thyroiditis; Autoantibodies; thyroid nodule; Thyrotropin; jodidperoxidasa; Iron-Binding Proteins; Hashimotova nemoc; autoprotilátky; thyreotropin; ženské pohlaví; lidé; thyroid cancer; Incidence; Thyroglobulin; Male; Retrospective Studies; Thyroid Gland; Female